Modeling Building Classes Using Moment Matching. Issue 1 (February 2016) - Cho, In Ho; Porter, Keith
Large-scale earthquake risk assessment necessitates models of the seismic performance of building classes. This work addresses how to depict a class with only a few (index) buildings whose designs span the attributes that most impact the seismic behavior of the class. We propose a general numerical moment matching (MM) technique to represent those seismic attributes of index buildings, which can then be individually analyzed by second-generation performance-based earthquake engineering methods (PBEE-2). The results probabilistically combined to model the class behavior as a whole. Thereby, the model honors the joint distribution of variable features within the class and propagates all other uncertainties that PBEE-2 already recognizes. Importantly, we can reflect and propagate with rigor the uncertain attributes of buildings within a class, notably without resorting to standard distributions. The MM enables PBEE-2 to rigorously capture seismic risk assessment of a building class.